The Effect of TPSq and TPS Strategy on Students’ Speaking Skill Viewed from Students’ Motivation - Hilma Pami Putri (Politeknik Negeri Padang, 2016)
This research was aimed to investigate the effect of think pair square and think pair share strategy on students’ speakingskill of describing things viewed from students’ motivation. This research employed 2 x 2 factorial design and involved the studentsof SMK YPM Zain Pauh Kambar, Padang Pariaman. The samples were chosen by using purposive sampling. The data were gainedthrough speaking test and analysed by using appropriate quantitative methods. The result of the research showed that think pairsquare and think pair share strategy were able to improve students’ speaking skill. There was an interaction between teachingstrategy and students’ motivation of speaking skill. Hence, it can be concluded that these two strategies can be used as alternativestrategies to enhance students’ speaking skill, and that they can enrich students’ experience to do other cooperative learningstrategies.